2022
DOI: 10.1186/s40634-022-00477-9
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of primary osteoblasts to combined magnetic and electric fields induced spatiotemporal endochondral ossification characteristic gene- and protein expression profiles

Abstract: Purpose Molecular processes in primary osteoblasts were analyzed in response to magnetic and electric field exposure to examine its potential impact on bone healing. Methods Primary osteoblasts were exposed to a combination of a magnetic field and an additional electric field (EFMF) (20 Hz, 700 mV, 5 mT, continuous sinusoids) in vitro. mRNA- and protein-expressions were assessed during a time interval of 21 days and compared with expression data ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…This study demonstrated the effect of CEMF therapy on the acceleration and enhancement of the bone healing process overall in a standardized osteotomy model in sheep, resulting in more mature new bone structure, callus morphology and superior biomechanical properties. It was hypothesized, based on in vitro findings using the CEMF technology [ 26 ], that CEMF treatment would enhance bone healing in vivo. The CEMF technology showed a significant effect in the 17-mm at 12 weeks compared to the 3-mm model at 9 weeks, in which means may have been higher in the CEMF group, but higher variability in responses rendered the differences not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated the effect of CEMF therapy on the acceleration and enhancement of the bone healing process overall in a standardized osteotomy model in sheep, resulting in more mature new bone structure, callus morphology and superior biomechanical properties. It was hypothesized, based on in vitro findings using the CEMF technology [ 26 ], that CEMF treatment would enhance bone healing in vivo. The CEMF technology showed a significant effect in the 17-mm at 12 weeks compared to the 3-mm model at 9 weeks, in which means may have been higher in the CEMF group, but higher variability in responses rendered the differences not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…It may involve a spectrum of responses, as the therapy was applied starting at day 4 postoperatively and therefore bridged various stages of bone healing, from inflammation to remodeling [ 4 ]. In vitro tests performed on the same CEMF technology showed evidence of enhanced osteoblast proliferation and osteogenic protein expression [ 26 ], which merit future investigation in a large animal model. Another limitation was the sample size ( n = 6), which, combined with the biological variability expected in sheep, made it difficult to detect statistical differences, particularly in the 3-mm gap model.…”
Section: Discussionmentioning
confidence: 99%
“…It may involve a spectrum of responses, as the therapy was applied starting at day 4 post-operatively and therefore bridged various stages of bone healing, from in ammation to remodeling (4). In vitro tests performed on the same CEMF technology showed evidence of enhanced osteoblast proliferation and osteogenic protein expression (29), which merit future investigation in a large animal model. A methodological limitation to note was that some semi-quantitative scores were not designed to distinguish between various advanced stages of maturation in bone healing and exhibited a ceiling effect.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have attempted to better understand the effects of a variety of electromagnetic field intensities over variable periods of time on animals [ 134 , 135 , 136 , 137 , 138 , 139 , 140 ], animal tissues [ 141 ], and cells [ 142 , 143 ]. The recent review by Lee et al [ 140 ] provides an excellent summary of much of the animal literature in this regard.…”
Section: Additional Risks Of Space Flight Into Deep Space and Living ...mentioning
confidence: 99%